Biological traits of six sterile oat biotypes in response to planting time. (20th January 2021) - Mahajan, Gulshan; Chauhan, Bhagirath S.
Abstract: Sterile oat ( Avena ludoviciana Durieu) is a problematic weed in winter crops of Australia. Biotypes of sterile oat adapted to the local environment may vary in environmental plasticity, which could increase their invasiveness. A 2‐yr (winter growing seasons of 2018 and 2019) study in Australia investigated the influence of planting date (early, mid‐, and late season) on the growth and reproduction potential of six biotypes (AL2/17, AL3/17, AL4/17, AL5/17, AL6/17, and AL9/17) of sterile oat. Averaged across biotypes, the seed production of sterile oat was reduced by 21 and 84% for mid‐ and late planting, respectively, compared with early planting (2, 660 seeds plant −1 ). Seed production was highly correlated with the first panicle emergence for early planting. However, for mid‐ and late‐season planting, seed production was correlated with panicle number and plant biomass. For mid‐season planting, taller plants had more seed number plant −1 than shorter plants. The results of this study imply that biotypes of sterile oat differ in environmental plasticity and that they can complete their life cycle under a wide range of temperatures in the winter season and contribute to its reinfestation. Results also suggest that early and mid‐season cohorts are prolific in seed production; however, late cohorts can also produce sufficient seeds for reinfestation. Therefore, integrated weed management strategies must be focussed on those tactics (manipulation of sowing time and row spacing) that could create a competitive crop environment and to suppress the growth of early cohorts of sterile oat to reduce their seed production. Core Ideas: Sterile oat is a problematic weed in winter crops of Australia. Early and mid‐cohorts of sterile oat are prolific in seed production. Seed production in early cohorts was correlated with time of first panicle emergence; however, in mid‐cohorts, it was correlated with plant height, panicle number, and plant biomass.